Mutations in FASTKD2 are associated with mitochondrial disease with multi‐OXPHOS deficiency. Issue 5 (30th January 2020) - Wei, Xiujuan; Du, Miaomiao; Li, Dongxiao; Wen, Shumeng; Xie, Jie; Li, Yuanyuan; Chen, Aolong; Zhang, Kun; Xu, Pu; Jia, Manli; Wen, Chaowei; Zhou, Huaibin; et al.
Abstract: Mutations in FASTKD2, a mitochondrial RNA binding protein, have been associated with mitochondrial encephalomyopathy with isolated complex IV deficiency. However, deficiencies related to other oxidative phosphorylation system (OXPHOS) complexes have not been reported. Here, we identified three novel FASTKD2 mutations, c.808_809insTTTCAGTTTTG, homoplasmic mutation c.868C>T, and heteroplasmic mutation c.1859delT/c.868C>T, in patients with mitochondrial encephalomyopathy. Cell‐based complementation assay revealed that these three FASTKD2 mutations were pathogenic. Mitochondrial functional analysis revealed that mutations in FASTKD2 impaired the mitochondrial function in patient‐derived lymphocytes due to the deficiency in multi‐OXPHOS complexes, whereas mitochondrial complex II remained unaffected. Consistent results were also found in human primary muscle cell and zebrafish with knockdown of FASTKD2 . Furthermore, we discovered that FASTKD2 mutation is not inherently associated with epileptic seizures, optic atrophy, and loss of visual function. Alternatively, a patient with FASTKD2 mutation can show sinus tachycardia and hypertrophic cardiomyopathy, which was partially confirmed in zebrafish with knockdown of FASTKD2 . In conclusion, both in vivo and in vitro studies suggest that loss of function mutation in FASTKD2 is responsible for multi‐OXPHOS complexes deficiency, and FASTKD2 ‐associated mitochondrial disease has a high degree of clinical heterogenicity. Abstract : Mutations in FASTKD2 are previously associated with isolated mitochondrial complex IV deficiency. Here, we identified three novel FASTKD2 mutations, c.808_809insTTTCAGTTTTG, homoplasmic mutation c.868C>T, and heteroplasmic mutation c.1859delT/c.868C>T, in patients with mitochondrial encephalomyopathy. Mutations in FASTKD2 were found associated with decreased level of mitochondrial 16S rRNA and multi‐OXPHOS deficiency in patients‐derived immortalized lymphocytes. Moreover, patient with FASTKD2 mutation can show sinus tachycardia and hypertrophic cardiomyopathy, which was partially confirmed in zebrafish with knockdown of FASTKD2.